Basin-level use and productivity of water: examples from South Asia - Molden, David J.; Sakthivadivel, Ramaswamy; Habib, Z. (International Water Management Institute, 2001)
Discusses and illustrates concepts for identifying ways of improving productivity of water within basins. The results of applying a water accounting procedure to four sub-basins in South Asia (Bhakra in India; Chishtian in Pakistan; Huruluwewa in nothern Sri Lanka; and Kirindi Oya in southern Sri Lanka) are presented. The methodology used identifies the quantities and productivity of various uses of water within a basin. This information is then used to identify the water-saving potential, and the means of improving the productivity of the managed supplies.